Generating the New Dimensions of Social Sustainability into Sustainable Urban Development Policy - Lydia Aulia Kumara; Dyah Mutiarin (Policy & Governance Review, 2019)
This paper contributes to the debates on how policy makers face the dilemma on sustainable urban development policies, by addressing social sustainability dimensions. Therefore, it aims to generate out the new dimensions of social sustainability into policy for sustainable urban development. The comprehension gives an insight that favor multi-disciplinary themes, in which it may support national political agenda, particularly in the realms of urban development. Hereby, the research methodology is mapping review; which is held by classifying a new model of social sustainability dimensions. This alternative was proposed to undertake more pressing urgencies in sustainable urban development. Moreover, the study is expected to overcome the ambiguous and complicated elements or key features in determining social sustainability. In general, an implication for urban society is that the new model of social sustainability can be directed to better improve the urban societal development, based on the state of well-being and humane principals.